Essays for truth seekers : a collection of essays and research on regional and global issues affecting the Arab World / [Khalaf Al Habtoor, Linda S. Heard, Paul Findley] - 495122 Al Habtoor, Khalaf; Heard, Linda S; Findley, Paul, 1921-; Al-Habtur, Majmuat (Dubai : Al Habtour Group, 2006)
PSZJBL